2004
DOI: 10.1097/01.brs.0000109883.18015.b9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Amicar on Perioperative Blood Loss in Idiopathic Scoliosis:

Abstract: The results of this study confirmed that the use of intraoperative Amicar is a safe, effective, and inexpensive method to significantly reduce perioperative blood loss in patients with idiopathic scoliosis undergoing posterior spinal fusion and segmental spinal instrumentation. The results have allowed us to reduce our recommendation for perioperative autologous blood donation, thereby further decreasing costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(42 citation statements)
references
References 19 publications
2
39
1
Order By: Relevance
“…By local cooling hematoma formation can be reduced by decreasing RBBF. In clinical practice, bleeding control of cancellous bone can only be achieved by application of bone wax, Gelfoam paste, Amicar, and therapeutic angiography . In this regard, local cooling would be a sufficient method to reduce bone bleeding reliably by decreasing bone blood flow after surgery—so far ice application is mainly performed to decrease pain, but not to affect blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…By local cooling hematoma formation can be reduced by decreasing RBBF. In clinical practice, bleeding control of cancellous bone can only be achieved by application of bone wax, Gelfoam paste, Amicar, and therapeutic angiography . In this regard, local cooling would be a sufficient method to reduce bone bleeding reliably by decreasing bone blood flow after surgery—so far ice application is mainly performed to decrease pain, but not to affect blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…We did not analyze the factors contributing to intraoperative blood loss, and this could be a limitation of this study. Considering that intraoperative blood loss is an important factor effecting postoperative blood loss, the use of antifibrinolytic or hemostatic agents proven to be effective in reducing postoperative blood loss [18-20] may be useful in case of heavy bleeding during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(710) In addition, several of these studies have significant limitations that may jeopardize the validity of their results. For example, of the three randomized trials that have evaluated the effect of EACA on RBC transfusion requirements in patients undergoing spinal surgery (79), one evaluated pediatric scoliosis patients and concluded that EACA was an effective method to significantly reduce perioperative blood loss and autologous transfusion requirements, however none of these patients received an allogeneic transfusion. (9) Two studies (78) concluded that EACA did not reduce transfusion exposure; however these studies included fewer patients than our study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, of the three randomized trials that have evaluated the effect of EACA on RBC transfusion requirements in patients undergoing spinal surgery (79), one evaluated pediatric scoliosis patients and concluded that EACA was an effective method to significantly reduce perioperative blood loss and autologous transfusion requirements, however none of these patients received an allogeneic transfusion. (9) Two studies (78) concluded that EACA did not reduce transfusion exposure; however these studies included fewer patients than our study. The remaining study (10) used a historical control and the observed benefit of EACA may have been due to improvements in surgical treatment, patient selection, or changes in criteria for transfusion between the treatment periods.…”
Section: Discussionmentioning
confidence: 99%